ASEAN-FTA Impact on Rubber and Crude Palm Oil Export: An Empirical Evidence from IMT Countries - Isnurhadi Isnurhadi; Abdul Bashir; Suhel Suhel (Integrated Journal of Business and Economics (IJBE), 2023)
This study applies the gravity model to explore whether the establishment and the agreement of the ASEAN Free Trade Area (AFTA) have an impact on the export increase of rubber and crude palm oil commodity trade for the case ASEAN member countries namely, Indonesia-Malaysia-Thailand (IMT). The study uses time-series data, first for Indonesia using the period of 1996-2017 with trading partners as much as 21 countries for crude palm oil (CPO) commodity and 22 countries for rubber commodity. Secondly, the CPO export model for Malaysia using data during 1997-2017 with 23 trading partners countries. Thirdly, export rubber model for Thailand using a period of 1999-2017 with 16 trading partners countries. The estimate the Indonesian and Thailand export model for rubber commodity, and second, the same model also is estimated export CPO for the Indonesian and Malaysian. Generally, we found that the regression results it appears ASEAN member countries have not been fully benefited from the enactment of the AFTA, especially on the export of Indonesia's main commodities such as rubber and crude palm oil which destined for trading partners countries. As for the export of Thailand rubber and Malaysian crude palm oil, both countries are still relatively slightly better because the AFTA agreement has fully benefited. During the study period, the results of this study indicated that these three countries trade both commodities more intensely to the non-ASEAN countries